PERANCANGAN AMBIENT MEDIA SEBAGAI MEDIA KAMPANYE PENCEGAHAN KEKERASAN DAN PELECEHAN SEKSUAL DI LINGKUNGAN KAMPUS - Tommi (Kartala, 2023)
The phenomenon of sexual violence and harassment can happen anywhere and by anyone. This phenomenon often occurs also in educated environments, one of which is the campus. Ideally the place is the safest place to gain knowledge for students. So that further education is needed about this phenomenon through social campaigns on campus. So that in the future this phenomenon can be prevented, a solution is made by using ambient media in elevators as design media in social campaigns about violence and sexual harassment in the campus environment. So it is hoped that the messages through this campaign can be conveyed properly and quickly understood by students, which can prevent acts of violence and sexual harassment in the campus environment.